A Pinch of Skin andA Scar that Remains: Examining Female Genital Mutilation in Sudan, Somalia and Saudi Arabia with Reference to Select Literary Works - Easo, Reshma Sarah; Muraleedharan, Sreenath (International Journal of Psychosocial Rehabilitation, 2020)
Female Genital Mutilation (FGM) is a horrendous practice that causes harm to the female genitalia in the name of customs and traditions. Tracing its roots before the arrival of Abrahamic religions, this pharaonic tradition is a strict violation against girls and women. With more than 3 million girls cut every year, United Nations has declared FGM as a ritual that needs to be eliminated. The practice has a very high incidence in some Middle Eastern as well as African countries. This paper tries to understand the type 3 cutting which is also known as infibulation occurring in Sudan, Somalia and Saudi Arabia. The paper also probes reasons as to why this ancient practice still thrives in these countries with the help of works written by WarisDirie, Mende Nazer and Jean Sasson.